A Remarkable Coexistence of Systemic Capillary Leak Syndrome and Diabetes in an 11-Year-Old Boy: A Case Report and Review of the Literature - Aysun Ata; Samim Özen; Damla Gökşen; Neslihan Edeer Karaca; Güzide Aksu; Necil Kütükçüler; Hüseyin Onay; Şükran Darcan (Case Reports in Immunology)
Systemic capillary leak syndrome (ISCLS) is a rare disease characterized by unexplained reversible capillary hyperpermeability followed by hypoperfusion, hemoconcentration, and either hypoalbuminemia or total hypoproteinemia. An 11-year-old boy was admitted with vomiting, generalized edema, and hyperglycemia, which was preceded by 5 days of coryzal symptoms, lethargy, and oral aft, without fever. On physical examination, he had tachycardia and hypotension, with severe generalized systemic nonitchy edema, and the laboratory tests supported the conclusion that he had severe hemoconcentration with hemoglobin: 184 g/L, hematocrit: 51.3 %, urea: 20 mmol/L, blood glucose: 11.1 mmol/L, and albumin: 19 gr/L, with normal urine analysis. On the fourth day, the patient was diagnosed with ISCLS, by ruling out other causes of shock and hypoalbuminemia. Intravenous immunoglobulin (IVIG) treatment regimen was administered on two consecutive days (day five and day six). His edema decreased on the fifth day, and the patient was deemed clinically well. There was no compartment syndrome, rhabdomyolysis, or pulmonary edema in the recovery period. However, respiratory virus panel PCR was positive for respiratory syncytial virus (RSV) and enterovirus, which were thought to be the triggering cause of ISCLS. For the differential diagnosis of diabetes, his fasting serum glucose was 13.4 mmol/L, simultaneous C-peptide was 0.44 nmol/L, and HbA1c was 64 mmol/mol, and urine ketone was positive. However, antiglutamic acid decarboxylase, anti-insulin antibody, and islet cell antibody were negative. At the last outpatient visit, 22 months after the diagnosis, his insulin dose was still 0.4 IU/kg/day and HbA1c was 40 mmol/mol, and without prophylaxis, there was no ISCLS attack. Conclusion. Early recognition of ISCLS is important for therapeutic awareness, since it is very rare in childhood and occurs usually without any prior provoking factors in healthy children. With the increase in awareness of the disease, knowledge and experiences about pediatric patients may also increase. We think that our case will contribute to the literature since there have been no pediatric diabetic patients with ISCLS reported.